Do Vary of English Shows Good For the Children during Stay at Home?: A Library research - Tanasy, Novalia; Aisyah, Sitti; Nashruddin, Nashruddin (Utamax : Journal of Ultimate Research and Trends in Education, 2021)
Children can naturally acquire languages easily and quickly even without formal teaching from teachers. English shows provided the children new knowledges and updates without leaving the comfort of their homes due to lock down. This study was designed to analyse the use of English shows to build the children’s English developmental for learning English as foreign language, including discussion of its advantages and weaknesses. Library research and qualitative method were used to explain the findings. The data collection was documented from 3 working papers, 25 journal articles and 4 renowned books related to the topics. The analysis reveals that the children were able to retell the shows scenes, characters, topics, stories, opinions and they can pronounce English words alike as the natives do. From English shows, the children can learn some positives values and habit from the characters. The weaknesses of this strategy is control means that parents must spare time to accompany their children while watching the shows which may boring and tiring them. The other weakness is cultural shock. The English shows were mostly created by American and European whom have different basic cultures from Indonesian, therefore parents must ready to explain some scenes which are unfamiliar to ours. Lastly, watching English shows from television and YouTube also considered as more expensive instead of learning from classroom since it still need payment, subscription, fast internet connection, gadget and electricity.